STRATEGI HUBUNGAN SUAMI ISTRI LONG DISTANCE RELATIONSHIP (LDR) PADA KELUARGA TENTARA NASIONAL INDONESIA (TNI) WING III PASKHAS BATALYON KOMANDO 465 BRAJAMUSTI PONTIANAK - Linda Ekaningrum, Fitri Sukmawati, Amalia Irfani (J-MD Jurnal Manajemen Dakwah, 2023)
Abstract: Long Distance Relationship (LDR) Strategies in the Family of the Indonesian National Armed Forces (TNI) from the 3rd Wing of a Special Team of the 465th Command Battalion Brajamusti Pontianak: Islamic Guidance and Counseling Study Program. Faculty of Ushuluddin, Adab and Da'wah (FUAD) State Islamic Institute (IAIN) Pontianak, 2021. This study aimed to find out: 1) How the Indonesian National Armed Forces families maintain their relationship while undergoing long-distance marriages; 2) The media used in the process of undergoing a long-distance marriage; 3) The process of communication in a long-distance marriage. This study uses qualitative-descriptive research. The data sources of this study consist of primary data sources and secondary data sources. Data collection techniques used in this study are observation, interviews, and documentation. While the researcher took an interactive model to analyze the data. The results of this study indicate that: 1) How to maintain relationships during the long- distance marriages which is carried out by Indonesian National Armed Forces (TNI) families, namely there are three ways, the first is good communication, the second is the commitment between husband and wife, then the third is mutual trust between husband and wife; 2) The media used by Indonesian National Armed Forces (TNI) wives when undergoing long-distance marriages are mobile phones, video calls, and other social media such as WhatsApp; 3) The process of communication in marriage at a distance that the wives of the Indonesian National Armed Forces (TNI) do is: It was mostly communication at night because it was time to relax and there was no work to care of. Then the problem that occurs when communicating is a bad signal condition. Keywords: Husband and Wife Relationship Strategy; Long Distance Relationship; Indonesian National Armed Forces Family.